Theory of Change in Digital Behavior Change Interventions (Dbcis) And Community-Based Change Initiatives – A General Framework - Rad, Dana; Rad, Gavril (Technium Social Sciences Journal, 2021)
A theory of change is a purposeful model of how an initiative, such as a policy, a strategy, a program, a project or an intervention contributes through a chain of early and intermediate outcomes to the intended result. Theories of change help navigate the complexity of social change. Digital behavior change interventions (DBCIs) and Community-based change initiatives represent complex designable systems. The goal of the DCBI is to provide an effective theoretical framework for behavioral change to practitioners that offer different forms of psychological intervention based on scientifically validated practices. Applying theory of change when designing digital individual and community interventions for optimizing digital wellbeing helps practitioners to achieve results in practice, as this strategic approach is generally considered an evidence-based framework. Theory of change is useful to guide the strategic thinking and action, as most of DCBI/ Community-based change initiatives research endeavors are active in a complex situation, often unplanned events happening. Conclusions and implications are discussed.